Somatostatin receptors in resected hepatocellular carcinoma: status and correlation with markers of poor prognosis. Issue 3 (10th November 2016) - Lequoy, Marie; Desbois‐Mouthon, Christèle; Wendum, Dominique; Gupta, Vandana; Blachon, Jean‐Luc; Scatton, Olivier; Dumont, Sylvie; Bonnemaire, Mireille; Schmidlin, Fabien; Rosmorduc, Olivier; Fartoux, Laetitia
Abstract : Aims: To investigate the status of somatostatin receptors (SSTRs) in resected hepatocellular carcinoma (HCC). Methods and results: Transcript and protein levels of SSTR2, SSTR3 and SSTR5 were investigated, with real‐time polymerase chain reaction (PCR) and manual and automated immunohistochemistry (IHC), in 53 resected HCCs and paired non‐tumour tissues. SSTR1, SSTR4, SSTR5TMD4 and SSTR5TMD5 were analysed with real‐time PCR. SSTR3 and SSTR5 transcripts were expressed in ~25% of HCCs, but not in adjacent non‐tumour tissues. SSTR1 and SSTR2 transcripts were overexpressed in 42% and 32% of HCCs, respectively. SSTR4, SSTR5TMD4 and SSTR5TMD5 were not detected. Membrane staining for SSTR2 was detected in 38% of HCCs, whereas SSTR5 protein was detectable in only 11% of HCCs. SSTR3 protein was detected in the majority of HCCs and adjacent non‐tumour liver tissues, but membrane staining was <20% of that in HCCs. The results obtained with the two IHC methods were highly correlated ( P < 0.0001). Statistical analyses also showed a positive correlation between SSTR2 membrane staining and cytokeratin 19 expression ( P = 0.04), serum α‐fetoprotein level ( P = 0.002), and poor differentiation ( P = 0.05). Conclusions: Membrane SSTR2 is detected reliably in HCCs by IHC, and is a potential therapeutic target, as it is coexpressed with markers of poor prognosis.